Occurrence of Indicator Genes of Antimicrobial Resistance Contamination in the English Channel and North Sea Sectors and Interactions With Environmental Variables - Bourdonnais, Erwan; Colcanap, Darina; Le Bris, Cédric; Brauge, Thomas; Midelet, Graziella (Frontiers in Microbiology, 2022)
Marine environment is a potential natural reservoir of antimicrobial resistance genes, subject to anthropogenic effluents (wastewaters, industrial, domestic), and known as a final receiving system. The aim of this study was to investigate the abundance and geographical distribution of three blaTEM, sul1 and intI1 genes, proposed as indicators of contamination to assess the state of antimicrobial resistance in environment, added to tetA gene and the microbial population (tuf gene) in the English Channel and North Sea areas. Bacterial DNA were extracted from 36 seawater samples. The abundance of these genes was determined by qPCR and was analyzed in association with environmental variables and geographical locations to determine potential correlations. The blaTEM and tetA genes were quantified in 0% and 2.8% of samples, respectively. The sul1 and intI1 genes were detected in 42% and 31% of samples, respectively, with an apparent co-occurrence in 19% of samples confirmed by correlation analysis. The absolute abundance of these genes was correlated with the microbial population, with results similar to the relative abundance. We showed that the sul1 and intI1 genes were positively correlated with dissolved oxygen and turbidity, while the microbial population was correlated with pH, temperature and salinity in addition to dissolved oxygen and turbidity. The three tetA, sul1 and intI1 genes were quantified in the same sample with high abundances, and this sample was collected in the West Netherlands coast area. For the first time, we have shown the impact of anthropogenic inputs (rivers, man-made offshore structures, maritime activities) and environmental variables on the occurrence of three indicators of environmental contamination by antimicrobial resistance in the North Sea and English Channel seawaters.